2022
DOI: 10.1136/jnis-2022-019489
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy for acute ischemic stroke in patients with active malignancy: a meta-analysis with trial sequential analysis

Abstract: BackgroundActive malignancy has a poorer prognosis and more deaths in patients with acute ischemic stroke (AIS). The outcomes of endovascular therapy (EVT) remain controversial in patients with AIS and active malignancy.MethodsWe searched PubMed, Cochrane, and Embase for articles published up to June 1, 2022. The primary outcome was good functional outcome at 3 months and successful reperfusion between patients with cancer and AIS and control patients. The secondary and safety outcomes included mortality at 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…AIS is also more likely to occur in cancer patients [ 21 ]. Patients with active malignancies have poorer functional outcomes and higher mortality rates than patients without active malignancies, even after reperfusion therapy [ 22 ]. Our study also found a significantly lower white blood count in the thrombocytopenia group, which could be explained by the white blood count platelet complex hypothesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIS is also more likely to occur in cancer patients [ 21 ]. Patients with active malignancies have poorer functional outcomes and higher mortality rates than patients without active malignancies, even after reperfusion therapy [ 22 ]. Our study also found a significantly lower white blood count in the thrombocytopenia group, which could be explained by the white blood count platelet complex hypothesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is well known that the coexistence of cancer and stroke is often observed, acute stroke patients with cancer undergoing EVT are not uncommon, as seen by the fact that approximately 6%-7% of all stroke EVT cases reportedly have cancer. [6][7][8] This review outlines the mechanisms of ischemic stroke in patients with cancer (in this review, ischemic stroke occurring in patients with active cancer are referred to as cancer-associated stroke); the efficacy of EVT; treatment strategies, including preprocedural evaluation; and prevention of recurrence after reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%
“…1–7 Two study-level meta-analyses did not show significant differences in 3-month disability, rates of symptomatic intracranial hemorrhage (sICH), or mortality between iPCAO patients treated with EVT and those with MM. 8,9 The largest patient-level analysis, involving 1023 iPCAO patients from the endovascular therapy of PLATO (Posterior Cerebral Artery Occlusion Stroke) collaboration, found that patients treated with EVT and MM had similar 3-month disability, without any significant difference on the distribution of the modified Rankin Scale (mRS). However, a higher proportion of patients treated with EVT had early neurological improvement and achieved excellent 3-month outcome (mRS score 0–1), yet with higher rates of sICH.…”
mentioning
confidence: 99%